A cultura do lúdico: brincadeiras musicais tradicionais da infância em um contexto do ensino fundamental - Rodrigo Duarte Portela (2018)
This research seeks primarily at understanding what constitutes the traditional childrens musical games and the meanings they acquire for children between six and eight years old, in the context of a public school of Belo Horizonte/MG. The purpose is to comprehend in which ways and in what circumstances children in this context appropriate such games, how they learn and teach to each other, as well as how childrens relations are affected by them. In order to achieve this purpose, the ethnographic perspective in education was taken as methodology. The investigation of the moments of playing in the school, in which children could choose to play, has revealed that children's play situations are permeated by innumerable questions related to sociability, gender issues, power relations and child development in many different aspects (affective, cognitive, social, cultural, artistic and others)